Digital Safety for Women and Children: Legal and Policy Challenges Indonesia, Philippines, and Thailand - Ahmad, Dwi Nur Fauziah; Smith, Nucharee Nuchkoom (Journal of Law and Legal Reform, 2024)
This study explores the legal protections against online sexual exploitation of children and online gender-based violence (OGBV) in Southeast Asia, focusing on Indonesia, the Philippines, and Thailand. Using a systematic literature review (SLR) methodology, this research identifies and evaluates legal frameworks, implementation challenges, and the role of digital platforms in addressing these issues. Key regulations such as the Electronic Information and Transactions (ITE) Law in Indonesia, the Cybercrime Prevention Act in the Philippines, and the Computer Crime Act in Thailand were analyzed alongside institutional reports and academic studies. The results reveal that while these countries have made significant progress through the establishment of legal frameworks, implementation remains hindered by limited technical capacity, a lack of digital forensic expertise, and low public digital literacy. Furthermore, weak enforcement and insufficient oversight of digital platforms exacerbate the problem, as many platforms fail to respond promptly to reports of illegal content. Despite progressive laws such as Indonesia's Sexual Violence Prevention Law and the Philippines' international collaborations, slow law enforcement processes and economic vulnerabilities contribute to the persistence of these issues. The study concludes that Southeast Asian countries need to enhance technical capabilities, expand public education, strengthen international collaboration, and ensure greater accountability from digital platforms. These measures are essential to addressing gaps in enforcement and creating a safer digital environment for women and children in the region.